2010
DOI: 10.1111/j.1365-2966.2010.16513.x
|View full text |Cite
|
Sign up to set email alerts
|

A wide field X-ray telescope for astronomical survey purposes: from theory to practice

Abstract: X‐ray mirrors are usually built in the Wolter I (paraboloid–hyperboloid) configuration. This design exhibits no spherical aberration on‐axis but suffers from field curvature, coma and astigmatism, therefore, the angular resolution degrades rapidly with increasing off‐axis angles. Different mirror designs exist in which the primary and secondary mirror profiles are expanded as a power series in order to increase the angular resolution at large off‐axis positions, at the expanses of the on‐axis performances. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…This approach was previously adopted to optimize the PSF across the FoV of X-ray grazing incidence telescopes by Conconi et al (2010). It follows a method that is similar to the Ritchey-Chretien design since on-axis aberrations are admitted in order to cancel off-axis aberrations and obtaining in that way a PSF response flat across the entire FoV.…”
Section: Astri Sst-2m Optical Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was previously adopted to optimize the PSF across the FoV of X-ray grazing incidence telescopes by Conconi et al (2010). It follows a method that is similar to the Ritchey-Chretien design since on-axis aberrations are admitted in order to cancel off-axis aberrations and obtaining in that way a PSF response flat across the entire FoV.…”
Section: Astri Sst-2m Optical Designmentioning
confidence: 99%
“…Wolter's approach was later adopted for the design of X-ray astronomical telescopes based on grazing incidence optics, and a number of X-ray telescopes were realized (Aschenbach 1985(Aschenbach , 2009. Following the approach initially suggested by Burrows et al (1992), Conconi et al (2010) showed that different Wolter-like designs could be obtained by expanding as a power series the primary and secondary mirrors' profiles in order to increase the angular resolution at large offaxis positions, at the expense of the on-axis performances. Also, the curvature of the focal plane could be optimized, similarly to Couder's solution for normal incidence mirrors.…”
Section: Introductionmentioning
confidence: 99%
“…A module design with mirror lengths scaled to the diameter has already been studied by Conconi et al (2010) to minimize the defocusing due to the field curvature in the WFXT telescope. Therefore, after choosing a sequence of mirror lengths according Eq.…”
Section: Design Of the Mirror Modulementioning
confidence: 99%
“…The current WFXT design is based on thin nested shells with polynomial profiles [3], radius-dependent length, and with the intersection planes between the two pseudo-cylindrical reflecting surfaces shifted one with respect to the other for each mirror shell. The result of the entire set of assembled shells assumes a sort of "butterfly-like" configuration [4]. The WFXT optical assembly will be composed by three identical modules, whose characteristics are reported in Table 1.…”
Section: Introductionmentioning
confidence: 99%